2019
DOI: 10.3390/su11143825
|View full text |Cite
|
Sign up to set email alerts
|

Reporting within the Corridor of Conformance: Managerial Perspectives on Work Environment Disclosures in Corporate Social Responsibility Reporting

Abstract: This paper examines managerial perspectives on work environment (WE) disclosures in corporate social responsibility (CSR) reports. WE encompasses all aspects of the design and management of the work system that affect the employees’ interactions with the workplace. The data are drawn from interviews with 20 CSR managers in large companies that are recognized as high performers in CSR. Managers reported that WE disclosures were an important part of CSR reporting and had several benefits—for example, it helped t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…As regards practical implications, given that companies face important challenges related to labour and human rights (Hess, 2019), and that LA&HR disclosures lack consistency and comparability (Kent Zunker, 2013;Dixon et al, 2019;Cahaya & Hervina, 2019;Tsalis et al, 2018), this study's findings suggest that companies, stakeholders, and society as a whole, would benefit from the greater presence of women in management teams. Those companies truly interested in complying with their social responsibilities should therefore incorporate a higher rate of women in management teams.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As regards practical implications, given that companies face important challenges related to labour and human rights (Hess, 2019), and that LA&HR disclosures lack consistency and comparability (Kent Zunker, 2013;Dixon et al, 2019;Cahaya & Hervina, 2019;Tsalis et al, 2018), this study's findings suggest that companies, stakeholders, and society as a whole, would benefit from the greater presence of women in management teams. Those companies truly interested in complying with their social responsibilities should therefore incorporate a higher rate of women in management teams.…”
Section: Discussionmentioning
confidence: 87%
“…The Global Reporting Initiative (GRI) developed a set of indicators to measure and report company performance in relation to labour practices and decent work (LA), and human rights (HR). However, despite this initiative, empirical studies found that the level and quality of LA&HR disclosure is low (Alawi & Belfaqih, 2019;Bowrin, 2018;Cahaya & Hervina, 2019;Cahaya et al, 2017;Koskela, 2014;Searcy et al, 2016;Tsalis et al, 2018), which limits the ability of stakeholders to assess corporate social performance (Dixon et al, 2019). Indeed, Cubilla-Montilla et al (2019) found that firms disclose less than 50% of the GRI indicators related to human and labour rights, and Cahaya et al (2017) reported that a lower percentage of listed companies disclose information regarding organisational health and safety.…”
Section: Labour and Human Rightsmentioning
confidence: 99%
“…Many companies report ordinarily or fulfill the requirement, while few companies fully follow the GRI standards with statistics. Previous research results show that labor disclosure has been briefly discussed and reported by large companies (Cubilla-Montilla et al, 2019;Dixon et al, 2019). In Pakistan, corporate sustainability reporting, such as labor disclosure, human rights, and product responsibility disclosure information, is in its early stages (Mahmood et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Since the reform and opening up, science and technology-based SMEs have gone through economic and institutional reforms successively, gradually ascending to the historical stage and becoming an important pillar of economic development and scientific and technological progress [1][2]. Science and technology-based SMEs are mainly distributed in emerging industries such as information technology, bioengineering, high-end equipment manufacturing, new energy, and new materials.…”
Section: Introductionmentioning
confidence: 99%